EKONOMI POLITIK MEDIA KOMODIFIKASI PEKERJA DALAM INDUSTRI MEDIA HIBURAN INDONESIA - Reza Aprianti (Wardah, 2013)
Political economy approach, see who the ruler of mass media sources of mass media production, distribution chain who is the holder of the mass media, who created the pattern of consumption over the mass media and other commodities as employment effects. Basically all of the above political economy of media can be created and arranged in such a way. By mastering the production of media sources, then it can determine its position in the industry.